Joyce and hagiography : saints above! - Schork, R. J., 1933- (Florida James Joyce series., 2000)
"R. J. Schork examines the function of the countless saints--genuine and bogus, famous and obscure, ancient and modern--who hover over James Joyce's fiction. Apostolic zealots, mutilated virgins, Celtic wanderers, stigmatic friars, Counter-Reformation founders, a hairy hermit, and Little Nelly of Holy God make their way through these pages, as do more fictitious heroes and heroines like St. Pseudonymous, St. Jingo, and St. Notwithstanding. Schork identifies them, traces their inspiration in Joyce's Irish Catholic upbringing, establishes their context in the Catholic tradition, and explores the mostly humorous and irreverent roles they play in Joyce's work"--Publisher